1999
DOI: 10.1007/s004270050252
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal control of ventral diaphragm myogenesis during metamorphosis of the moth, Manduca sexta

Abstract: Both the proliferation and differentiation of ventral diaphragm myoblasts are controlled by ecdysteroid during metamorphosis of the moth, Manduca sexta, but the responses have different hormonal requirements. Tonic exposure to moderate levels of ecdysteroid are required to stimulate myoblast proliferation. This is due to the presence of an ecdysteroid-dependent control point in the G(2) phase of the cell cycle. As a result, proliferation can be repeatedly turned on or off simply by adjusting the concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The mechanism by which these retraction-related genes are normally shut off has not been determined, but it may be triggered extrinsically by the high titers of 20E that are experienced early in adult differentiation (before 36 hr APF). JH might prevent the high 20E titers from suppressing these genes in a manner similar to that proposed for the hormonal control of ventral diaphragm muscle development in M. sexta (Champlin et al, 1999). In the later case, low levels of 20E permit the proliferation of myoblasts, whereas high levels cause proliferative arrest and muscle differentiation.…”
mentioning
confidence: 82%
“…The mechanism by which these retraction-related genes are normally shut off has not been determined, but it may be triggered extrinsically by the high titers of 20E that are experienced early in adult differentiation (before 36 hr APF). JH might prevent the high 20E titers from suppressing these genes in a manner similar to that proposed for the hormonal control of ventral diaphragm muscle development in M. sexta (Champlin et al, 1999). In the later case, low levels of 20E permit the proliferation of myoblasts, whereas high levels cause proliferative arrest and muscle differentiation.…”
mentioning
confidence: 82%
“…Other moths, like Manduca sexta, showed more subtle responses to allatectomy, with premature adult differentiation most evident in the patterned region of the compound eye, posterior to the morphogenetic furrow (Kiguchi and Riddiford, 1978;Champlin and Truman, 1998a). Subsequent studies on a variety of tissues in Manduca showed that the eye, the optic lobe and the ventral diaphragm each had a prolonged period of proliferation that extended from the prepupal period through early adult differentiation (Champlin and Truman, 1998a;Champlin and Truman, 1998b;Champlin et al, 1999). This proliferation was maintained by a-ecdysone or low levels of 20-hydroxyecdysone (20E), but was terminated by high levels of 20E, which induced differentiation.…”
Section: Research Articlementioning
confidence: 99%
“…This proliferation was maintained by a-ecdysone or low levels of 20-hydroxyecdysone (20E), but was terminated by high levels of 20E, which induced differentiation. These tissues are exposed to differentiation-inducing titers of 20E that occur during the larval-pupal transition early in their growth, but studies on the ventral diaphragm showed that JH 'protects' them from these high 20E levels, allowing them to continue proliferating (Champlin et al, 1999). Removal of JH resulted in these tissues undergoing premature termination of tissue growth and precocious adult differentiation.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, selective recognition of a variety of EcR response elements contributes additional specificity and functionality (7). A fine tuning of gene expression regulated by the ecdys-one receptor might also be achieved by different ecdysteroids (7,9) and even by the precursor hormone ecdysone, which was demonstrated to have an active role in stimulating cell proliferation during optic lobe neurogenesis in the moth Manduca sexta (10,11).…”
Section: Mostly In Their Different Contributions To Solvation/desolvamentioning
confidence: 99%